ISCL/EORTC-CLTG/USCLC recommendations for the diagnosis, staging and treatment of early-stage paediatric mycosis fungoides: a modified Delphi consensus : part two: treatment : guidelines - Hodak, Emmilia; Amitay-Laish, Iris; Bagot, Martine; Battistella, Maxime; Ben Amitai, Dan; Cozzio, Antonio; Duvic, Madeleine; Ferenczi, Katalin; Foss, Francine; Geskin, Larisa; Guenova, Emmanuella; Kim, Youn H; et al. (British journal of dermatology, 2025)
Paediatric mycosis fungoides (MF) is characterized by early-stage disease, a strikingly indolent course and high rates of unusual variants. Despite these clinical peculiarities and the special treatment-related safety considerations in children and adolescents, detailed published data on treatments of paediatric MF are scarce, and management is currently based primarily on standard practice in adults. The aim of this work was to develop treatment recommendations specifically designed for MF in children and adolescents, on behalf of the three largest societies for cutaneous lymphomas, the International Society for Cutaneous Lymphomas (ISCL), the European Organisation for Research and Treatment of Cancer - Cutaneous Lymphoma Tumour Group (EORTC-CLTG), and the United States Cutaneous Lymphoma Consortium (USCLC). We developed this guideline through an international expert consensus process and in accordance with the EQUATOR Network’s recommendations for guideline development. A modified Delphi process was conducted, using questionnaires covering treatment modalities that are recommended by international guidelines for adult MF. Two rounds of expert feedback were conducted, with an additional one hybrid consensus meeting. Therapeutic recommendations were formulated focusing mainly on early-stage disease. These recommendations take into account disease-specific parameters with therapeutic implications, including the specific stage of the disease, the type of lesion, and the presence of the folliculotropic variant, which is commonly observed in the paediatric age group. Patient-related factors, including safety concerns specific to this young age group, were also addressed. This ISCL/EORTC-CLTG/USCLC guideline provides up-to-date age-specific practical recommendations for the treatment of MF in children and adolescents.Mycosis fungoides (MF) is one of a group of skin cancers called skin lymphomas. MF in younger children is rare, and the disease is mostly managed as for adult patients. So far there are no detailed published recommendations tailored to paediatric MF. Thus, we base disease management on the standard treatments for adult MF. However, for several reasons we have to treat young patients with MF differently from adult patients. Most young patients with MF have early disease, which nearly always remains mild. Also, treatment benefits must be balanced against possible short- and long-term side-effects.We set out to develop a guideline for managing paediatric MF. We first established an international panel of experts from various medical specialties. We then used a special agreement process to develop recommendations.We focused on early-stage paediatric MF and reached agreement on the main treatment options. We recommend two broad types of therapy. First are ‘skin-directed therapies’, applied to the skin or using ultraviolet light. Second are drugs that affect the whole body. We recommend these for rare cases that do not respond well to skin-directed therapies.This guideline will help doctors choose the best therapy to treat young patients.